Assessing the impact of socially responsible human resources management on company environmental performance and cost of debt. (27th August 2021) - Gangi, Francesco; D'Angelo, Eugenio; Daniele, Lucia Michela; Varrone, Nicola
Abstract: This study answers the call for more in‐depth investigations into the antecedents and effects of corporate environmental responsibility (CER). In particular, we aim to verify whether socially responsible human resource management (SRHRM) positively affects the level of CER engagement and whether CER impacts firm financial performance. Based on a sample of 317 food companies, over the study period 2010–2017, we found that SRHRM improves CER engagement, both as a whole and with reference to its sub‐pillars. Furthermore, findings from the current study reveal that CER reduces the cost of debt and negatively moderates the positive effect of SRHRM on financial costs. The paper provides original implications concerning the complementarity between social and environmental activities and the benefits for firms to communicate their environmental performance to debt holders.